Recurrent births (multiparity) lead to permanent changes in cardiac structure - Yilmaz, Mucahid; Korkmaz, Hasan (Wiley, 2022)
Aim Although the effects of pregnancy on the cardiovascular system have been covered by many studies, permanent changes in the hearts of multiparous women have not been investigated. This study therefore aimed to examine the permanent structural changes in the cardiac structure of multiparous women via transthoracic echocardiography (TTE). Method This case-control study included 366 females who had given birth to 1-21 children, and 218 females with no previous deliveries. Anamnesis, physical examination, electrocardiography (ECG), TTE, and exercise stress tests were used to determine whether the cases had additional systemic pathologies. The structural cardiac parameters of all cases were recorded with TTE. Results The study revealed that LV mass, LV mass index, left ventricular end diastolic volume (LVEDV), left ventricular end diastolic volume index (LVEDVI) were observed higher in women with five or more deliveries when compared to nulliparous women. On the other hand, ejection fraction (EF) was significantly lower in the same group. Receiver operating curve (ROC) analysis demonstrated that the prediction sensitivity for the presence of eccentric hypertrophy was 74% among women who had given >10.5 births, and its specificity was 97.8% (AUC: 0.949, 95% CI 0.905-0.993; p < 0.0001). Conclusion The results showed that women with recurrent births had increased left ventricular end diastolic volume, left ventricular total mass in myocardium and decreased EF due to increased end diastolic volume. The results also showed delivering at frequent intervals (especially the birth of 11 or more) may be one of the causes of eccentric hypertrophy, in women of the low-to-middle income countries.
Keywords: eccentric hypertrophy; left ventricular end diastolic volume; left ventricular end diastolic volume index; LVmass; LVmass index; multiparity